The regional species richness and genetic diversity of A rctic vegetation reflect both past glaciations and current climate - Lærke Stewart; Inger G. Alsos; Christian Bay; Amy L. Breen; Christian Brochmann; Noémie Boulanger‐Lapointe; Olivier Broennimann; Helga Bültmann; Peder Klith Bøcher; Christian Damgaard; Fred J. A. Daniëls; Dorothee Ehrich; et al. (Global Ecology and Biogeography, 2016)
Aim The A rctic has experienced marked climatic differences between glacial and interglacial periods and is now subject to a rapidly warming climate. Knowledge of the effects of historical processes on current patterns of diversity may aid predictions of the responses of vegetation to future climate change. We aim to test whether plant species and genetic diversity patterns are correlated with time since deglaciation at regional and local scales. We also investigate whether species richness is correlated with genetic diversity in vascular plants. Location Circumarctic. Methods We investigated species richness of the vascular plant flora of 21 floristic provinces and examined local species richness in 6215 vegetation plots distributed across the A rctic. We assessed levels of genetic diversity inferred from amplified fragment length polymorphism variation across populations of 23 common A rctic species. Correlations between diversity measures and landscape age (time since deglaciation) as well as variables characterizing current climate were analysed using spatially explicit simultaneous autoregressive models. Results Regional species richness of vascular plants and genetic diversity were correlated with each other, and both showed a positive relationship with landscape age. Plot species richness showed differing responses for vascular plants, bryophytes and lichens. At this finer scale, the richness of vascular plants was not significantly related to landscape age, which had a small effect size compared to the models of bryophyte and lichen richness. Main conclusion Our study suggests that imprints of past glaciations in A rctic vegetation diversity patterns at the regional scale are still detectable today. Since A rctic vegetation is still limited by post‐glacial migration lag, it will most probably also exhibit lags in response to current and future climate change. Our results also suggest that local species richness at the plot scale is more determined by local habitat factors.

Analysis of the PKR-eIF2alpha phosphorylation homology domain (PePHD) of hepatitis C virus genotype 1 in HIV-coinfected patients by ultra-deep pyrosequencing and its relationship to responses to pegylated interferon-ribavirin treatment - F. Bolcic; M. Sede; F. Moretti; G. Westergaard; M. Vazquez; N. Laufer; J. Quarleri (Archives of Virology, 2012)